Perspectives of international enviromental law in the protection of tropical florests and the impact on the brazilian Amazonia and Atlantica Florest - Lisboa, Gabriel Esperança (2021)
The theme of this work deals with deforestation and the protection of tropical forests from the perspective of International Environmental Law and the impacts of this protection on the Brazilian Amazon and the Atlantic Forest. Thus, as a general objective, it is intended to conceptualize the tropical forest issue from the point of view of International Environmental Law, bringing negative and positive points of the impacts caused in Brazil. The theme is an urgent debate, since environmental policies to contain deforestation have changed since the Forest Code (2012), it can be inferred as a consequence the increase in rates of 20% of the deforested area of the Legal Amazon, between August 2018 to April 2019, when compared to the same period in the previous year, with Amazonas being one of the highest deforestation rates. (IMAZON, 2019). The problem of this study focuses on the issue of the Pilot Program and the application of international legislation, where, nevertheless, the program had points of success and failures, currently it has fallen by the wayside, given that the Brazilian government neglects the environmental protection of the Brazilian Amazon. To achieve the general objective, the research is dedicated to the survey of bibliographic and documentary reviews on international environmental law and the pilot program. This study aims to debate the deforestation and the protection of tropical forests from the perspective of International Environmental Law, expanding perceptions about the effects of international legislation. Given this, it is expected as a result of this research a survey of theoretical and documentary references and an analysis demonstrating the positive and negative impacts of international protection of tropical forests.